Developing an OPEN Framework for Asking EBLIP Questions in Open Education - Bell, Emilia C.; Stagg, Adrian (Evidence Based Library and Information Practice, 2026)
Objective – This paper proposes a novel framework for asking questions in evidence based library and information practice (EBLIP) called OPEN (Objective, Purpose, Evidence, and Narrative). It responds to the question: How can a framework for asking EBLIP questions be developed and applied to open educational practices (OEP)?Methods – Using a single-case study design, the framework was developed using an inductive approach throughout a three-year collaborative project to create a data dashboard. The project was documented, and these qualitative project artefacts were analyzed. The analysis was used to develop the framework and determine its value.Results – Arising concurrently from the data dashboard project, the OPEN framework comprises four elements - Objective: What do we need to know?; Purpose: Why do we need to know this?; Evidence: What evidence do I have or need?; and Narrative: How will I communicate this evidence? These elements guide library and information professionals to define what they need to know, collect, and communicate to make evidence based decisions. The case study demonstrates how the framework can be applied to OEP.Conclusion – Existing evidence based practice (EBP) frameworks developed for clinical environments are difficult to apply to the wide range of EBLIP initiatives, which are often more exploratory, or more immediate in their evidence needs. UniSQ Library's collaborative data dashboard project highlighted the need to develop a flexible framework that diverse stakeholders, including OEP practitioners, with differing levels of experience in evidence based practice, could apply. This research found that the collaborative and reflective nature of the project was instrumental in developing both a useful data dashboard to empower authors to tell their own data stories, and a new framework that contributes to the future of EBLIP and enhances the ability of OEP practitioners to meaningfully engage with EBP.